Present Participle in the English and Czech Fiction - Basetlíková, Jana (Univerzita Pardubice, 2012)
This Bachelor paper focuses on the syntactic functions of the present participle in fictional literature. There is also paid attention to the Czech equivalents of the present participle in the particular style. Firstly, the present participle is introduced as well as its syntactic functions. Then, the corpus of examples for the analysis is presented, analysed, discussed and compared with the Czech translation. A special attention is paid to the sentence condensation when one expects a variety of possible translations. The typological differences between the two languages, English and Czech, are also described because they are important for the analytical part of the paper.
Přítomné participium v anglické a české umělecké literatuře
Keywords: slovesa; fráze slovesa; finitní a nefinitní tvary; přítomné participium; nominální a analytická angličtina; verbální a syntetická čeština; kondenzace; umělecká literatura; české ekvivalenty; verbs; verb phrase; finite and non-finite forms; present participle; nominal and analytic English; verbal and synthetic Czech; condensation; fiction; Czech equivalents